DISTRIBUTION, HOROLOGY AND PREDICTIVE MODELING OF PUERARIA MONTANA VAR. LOBATA (WILLD.) SANJAPPA & PRADEEP IN BOSNIA AND HERZEGOVINA (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Pueraria, or kudzu (Pueraria montana var. lobata (Willd.) Sanjappa & Pradeep) is a dangerous invasive foreign species of the legume family (Fabaceae). It inhabits neglected, open, bright habitats of urban areas (neglected field land, railways, etc.) and forest edges. In many countries, it is characterized as a dangerous invasive species. Due to the great danger of endangering autochthonous diversity, the goal was to create a model of predictive distribution with regard to environmental factors in Bosnia and Herzegovina. Distribution data was taken from available literature sources, as well as our own field research. The model is made on the basis of climate substrates in the form of raster layers taken from the WorldClim database that are aligned to the same, resolution, size and coordinate reference system at a resolution of about 1x1 km. In addition to the climate variables, 20 m DEM and CLC 2018 data in the form of raster layers were also used. The obtained results indicate that the distribution of the given species in the area of the Neretva river basin, and the possibility of its expansion, is why it is necessary to implement adequate preventive measures. The variable Bio_9 (Medium temperature of the driest quarter) has statistically significantly the greatest impact on the habitat suitability of a given species.